The impact of a top player injury on Romanian National handball team performance at the France EHF EURO 2018 - Gheorghe, C.; Mereuta, C. (5th EHF Scientific Conference "Handball for Life", 21.-22.11.2019, Cologne, 2020)
The aim of this study is that of analyzing whether the injury suffered by the most valuable player of the Romanian National Team, in a key moment of the competition influenced the team's subsequent performance. Team efficiency has been analyzed, based on data provided by the European Handball Federation's website, as well as on data collected by the author by re-watching and reviewing the matches.